Plant Nitrogen Uptake From Insect Frass Is Affected by the Nitrification Rate as Revealed by Urease and Nitrification Inhibitors - Watson, Conor; Preißing, Timo; Wichern, Florian (Frontiers in Sustainable Food Systems, 2021)
Insect protein production is considered a sustainable alternative to livestock protein which furthermore utilizes waste streams. Its production can have positive but also potentially negative environmental effects, which require evaluation. Frass, the byproduct of insect production, is regarded an efficient organic fertilizer or soil amendment. However, several studies report negative frass effects on plant growth and nitrogen (N) cycling. Therefore, a pot trial was carried out which sought to understand N release from frass and subsequent growth and nutrient uptake of Italian ryegrass. Mealworm frass (MWF) or buffalo worm frass (BFW) was applied at two rates (1.5 and 3% w/w) to a soil-sand mix. To evaluate N release processes, frass was applied alone, with a nitrification inhibitor (NI), a urease inhibitor (UI), or both (NI+UI). Plant N, nutrient uptake and soil inorganic N were measured at the experiment's end. To gauge whether altered N fluxes induced changes in the microbial community, soil microbial biomass, bacterial/archaeal abundances and ergosterol content as a fungal biomarker, were determined. Both frass types and application rates stimulated microbial growth and N mineralization. The 3% rate inhibited seed germination, possibly due to salinity or ammonia toxicity. At the 1.5% rate, both frass types were effective fertilizers. MWF led to higher biomass and nutrient uptake, owing to its higher extractable nutrient concentrations. The 3% rate caused nitrite accumulation in the absence of NI. NI improved plant biomass, nutrient uptake, stimulated archaeal and bacterial abundances and prevented nitrite accumulation. UI reduced N mineralization, showing that a substantial fraction of frass organic N is ureic. UI enhanced fungal contribution to the microbial biomass, revealing the importance of bacteria in frass N mineralization processes when UI is not applied. NI and UI combined, induced greater N release from frass than UI or NI alone. Our study demonstrated the usefulness of NI and UI in studying N release from frass. NI can improve plant N uptake and minimize N losses following frass application, reducing its potentially negative effects. UI can retard N release from frass, allowing its application as a slow-release fertilizer, but should not be used concurrently with NI.